Azarias Ribeiro de Souza e José Luís de Mesquita: professores negros no sul de Minas Gerais - 1882/1954 - Lima, Andrêsa Helena de (2015)
The present work consists of a research entitled “Azarias Ribeiro de Souza and José Luis de Mesquita: black professors in Southern Minas Gerais – 1882-1954”, and has the objective of analyzing the trajectory of these professors, problematizing different social markers, such as race and ethnicity, social class and masculinity interconnected with education. The research was conducted focusing on Cultural and Post-structuralist Studies, reflecting on discourse; power relations; the role of intellectuals, thinking of movement in the gaps that allow us to question the education system, which can maintain or modify discourses depending on the political actions of professors acting in this front. We problematized produced knowledge and visualized the cons truction of identities by means of representation. With the objective of analyzing the life and work of black professors in Lavras, Minas Gerais, Brazil, we conducted bibliographical and document research regarding the acting of these professors. The research allowed us to infer the daily resistance of Azaria s Ribeiro de Souza and José Luis de Mesquita, their great insertions in the region of the municipality of Lavras, occupying decisive interlocution positions in schools, newspapers, clubs, bands, among others.